Etnomatematika pada Makanan Tradisional Melayu Daik Lingga Sebagai Sumber Belajar - Maghfiroh Sa Adatul Muk Minah; Nur Izzati (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2021)
The purpose of this study was to find mathematical activities in the Daik Lingga culture. This research focuses on the ethnomatematic exploration of the traditional Malay food of Daik Lingga which can be used as a source of learning mathematics. Daik's traditional food is generally made from sago. This research is a qualitative type and uses an ethnographic approach. The data collection technique was carried out by interviewing related sources and documentation. The data analysis technique was based on the design of Miles and Huberman by reducing data, presenting data, and concluding/ verification. Based on the results of data collection, there are several mathematical elements in the traditional Malay food of Daik Lingga. The mathematical elements contained include shapes (circles and right triangles), space shapes (cones), folding symmetry, reflection, rotation, acute angles, right angles, and parallel lines. Therefore, Daik Lingga's traditional food can be used as a source of interesting mathematics learning for students so that learning becomes meaningful.